Effect of Organic Manure on Nutrient Contents of Rice Grown in an Arsenic Contaminated Soil - Ashrafi, R; Biswas, MHR; Rahman, GKM Mustafizur; Khatun, R; Islam, MR (Bangladesh Journal of Scientific and Industrial Research, 2010)
A pot experiment was carried out to study the effects of organic manures on nitrogen, phosphorus, potassium and sulphur concentrations in grain, husk, stem and root of rice grown in an arsenic contaminated soil. Randomized Complete Block Design with three replications was followed where each pot received an equal amount of N, P, K and S to sustain normal plant growth. N, P, K and S concentration in grain, husk, straw and root of rice plant were increased with organic manure application compared to control treatment. This study considered rice husk and root along with grain and straw as they have value to increase soil nutrient by recycling. Arsenic contamination becoming a concerning issue because its contamination in many agricultural soil is increasing following contamination in groundwater. This study concluded that organic manure is effective in arsenic contaminated soil to increase N, P, K and S concentration in rice plant. Key words: Organic manure; Nutrient, Rice plant; Arsenic contaminated soil DOI: 10.3329/bjsir.v45i3.6526 Bangladesh J. Sci. Ind. Res. 45(3), 183-188, 2010